Persepsi Siswa SD Negeri 43 Siguntur Muda tentang Kontribusi Kepala Sekolah dan Guru terhadap Pemanfaatan Perpustakaan Sekolah - Salsabila, Shally; Marlini, Marlini (Scinary, 2023)
The background of this research is the lack of interest of students in using the library. The aim of the study was to describe students' perceptions of the principal's and teacher's contributions to library use and to look at the effect of the principal's and teacher's contributions on library use. The approach used is quantitative and causal-associative. 55 respondents became the sample taken by the stratified random sampling technique. The research instrument is a questionnaire. Data analysis techniques are used to see the description of the variables using the percentage formula and the average value. Meanwhile, to determine the effect of variables X1 and X2 on variable Y using multiple linear regression analysis, The results of the study are: (1) the principal's contribution is categorized as very low; (2) the teacher's contribution is categorized as moderate; (3) Students' use of the library is categorized as very low; (4) There is an Influence of the Contribution of the Principal, and There is No Influence of the Contribution of the Teacher on the Utilization of the Library.